Strategi Dakwah Islam dalam Pengembangan Seni dan Peradaban - Wildan Yahya (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2007)
As a distinctive feature of Islamic civilization, art become a way for communicating Islamic principles. The real essence of art is al-Tauhid which comes up from light chemical reactions. Al Tauhid has two aspects: the methodology and conceptual. The art of Islam itself has functions like these: reminder of tauhid, material transfiguration, structure transfiguration, and beauty.